Transformation of Academic Writing in the Digital Age - M. A. Safonova; A. A. Safonov (Высшее образование в России, 2021)
Retaining its unifying function in creating academic texts, academic writing is undergoing various changes brought about by digitisation. The key trends are related to three aspects of academic writing: formal bibliometrics, principles of collaboration, and interaction with the readers. The first trend concerns the growing importance of identifiers, citation standards, key words and other metadata that underlie the creation of data bases allowing universities and scientific centres to take administrative and organizational decisions. Secondly, information technologies for collaborative writing stimulate the shift from individual authorship to the collective one and from thematic collaboration to the functional distribution of authorship. Finally, academic writing has adopted marketing strategies and instruments in communicating scientific knowledge to the audience. Digitisation has caused the emergence of postproduction in academic writing, i.e. applying Internet resources to enhance the reach of one’s academic papers. These trends require a revision of the approach to teaching academic writing and a more profound study of the new phenomena conditioned by the digital era.